2015
DOI: 10.2903/sp.efsa.2015.en-795
|View full text |Cite
|
Sign up to set email alerts
|

Inventory and review of quantitative models for spread of plant pests for use in pest risk assessment for the EU territory

Abstract: This report considers the prospects for increasing the use of quantitative models for plant pest spread and dispersal in EFSA Plant Health risk assessments. The agreed major aims were to provide an overview of current modelling approaches and their strengths and weaknesses for risk assessment, and to develop and test a system for risk assessors to select appropriate models for application. First, we conducted an extensive literature review, based on protocols developed for systematic reviews. The review locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 115 publications
(83 reference statements)
0
26
0
Order By: Relevance
“…We model the spread of X. fastidiosa using a spatially explicit simulation model, building upon the spread model presented in Chapman et al (2015) (see Case Study 5), which we briefly describe in the sections below. The model runs over the Apulian region at a 1 km 2 gridded resolution and at a yearly temporal scale to correspond with the seasonality of the vector which only feeds on olive trees in the summer months when host grasses dry-out (EFSA PLH Panel (EFSA Panel on Plant Health) 2015).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…We model the spread of X. fastidiosa using a spatially explicit simulation model, building upon the spread model presented in Chapman et al (2015) (see Case Study 5), which we briefly describe in the sections below. The model runs over the Apulian region at a 1 km 2 gridded resolution and at a yearly temporal scale to correspond with the seasonality of the vector which only feeds on olive trees in the summer months when host grasses dry-out (EFSA PLH Panel (EFSA Panel on Plant Health) 2015).…”
Section: Methodsmentioning
confidence: 99%
“…progression of disease within the grid cell as a fraction of trees infected); and dispersal between grid cells. This approach is well suited to the underlying epidemiological mechanisms of vector spread and phenology (Chapman et al 2015; EFSA PLH Panel (EFSA Panel on Plant Health) 2015). Chapman et al (2015) showed that the model reproduces the qualitative patterns of X. fastidiosa spread in Apulia, Italy.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations